Effect additive of Albropouls and yeast in the concentration of reproductive hormones after weaning the Awassi lambs - Abed, Hadeel A. (Journal of Kerbala for Agricultural Sciences, 2016)
The study was conducted in animal field and laboratories which belonged to department of technical animal production , Al-musiab Technical College , to study the effect of Albropouls extract , yeast and to mix them in the concentration of some sexual hormone in Awassi lambs . The study included 24 lambs , aged ranged from 4-5 months for period from September to November 2015 . the results showed that the concentration of testosterone hormone at different treatment was significant difference (P<0.05) during the first , second and third months, and reaching the highest concentration in the third month in the treatment of the mixture (7.81 ng/ml؟8 mglmomths, and reaching the highest concentration in the third month , in the treatment of the mixture () some sexual hormone) . The results also showed that non-significant effect of treatments on the concentration of lutinizing and follicle stimulating hormones during first and second months , while there was a significant effect (P<0.05) in the third month in the concentration of both hormones , and the best concentration of both hormones were in the mixture treatment (4.16 and 3.93 ng/ml) respectively .It was concluded that importance of food additives during growth to improve the concentration of sexual hormones and that is reflected on the activity of reproductive physiology and speed up access to early puberty.